Odpowiedzi

2010-03-12T18:28:21+01:00
-6*7= -42
-8*(-9)=72
-12*(-4)= 48
24:(-3)=-8
-63:(-7)= 9

-5,4:2=-2,7
0:(-2,3)=0
6,6:(-3)=-2,2
-8:(-24)= 1/3
5,1*(-3)= -15,3

-10:(-2,5)=4
8*(-1 i 1/8)= -9
-2 i 1/2 *(-6)= 15
-3 i 3/4*(-6)=22,5
12:(-1 i 1/2)= -8
1 1 1
2010-03-12T18:31:02+01:00
2010-03-12T18:47:25+01:00
-6*7 = -42
-8*(-9) = 72
-12*(-4) = 48
24:(-3) = -8
-63:(-7) = 9

-5,4:2 = -2,7
0:(-2,3) = 0
6,6:(-3) = -2,2
-8:(-24) = 1/3
5,1*(-3) = -15,3

-10:(-2,5) = 4
8*(-1i1/8) = 8/1*(-9/8) = -9
-2i1/2*(-6) = 5/2*6/1 = 15
-3i3/4:(-6) = -15/4*-1/6 = 5/(4*2) = 5/8
12:(-1i1/2) = 12:-3/2 = 12*-2/3 = 4*-2 = -8